The Effect of Parental Attention, Home Study Facilities and Learning Motivation on Students Learning Outcome (Research : Social Sciense Subject in District Sungayang High School Tanah Datar Regency) - Najmi Yatul Fijar; Bustari Muchtar; Idris Idris (Universitas Negeri Padang, 2019)
This research was conducted to see how far the effect of parental attention, home study facilities and motivation on student learning outcome of social science subject on District Sungayang high school Tanah Datar regency. Descriptive associative method was used to conduct this research. The sample which was chosen by using proportional random sampling method. The collected data was analized stastiscally with path analysis. Thus, the result show that (1) parental attention gave a significant effect on student motivation, (2) home study facilities fgave a significat effect on student motivation, (3) parental attention gave a significant effect on students learning outcome, (4) home study facilities gave a significant effect on student learning outcome and (5) motivation gave a significant effect on student learning outcome